2022
DOI: 10.3389/fimmu.2022.826152
|View full text |Cite
|
Sign up to set email alerts
|

Rituximab in Systemic Lupus Erythematosus: Transient Effects on Autoimmunity Associated Lymphocyte Phenotypes and Implications for Immunogenicity

Abstract: B cell abnormalities are common in systemic lupus erythematosus (SLE), and include expansion of double negative (DN) and age-associated-like B cells (ABC-like). We aimed to investigate rituximab (RTX) effects on DN and ABC-like B-cell subsets and, when possible, also secondary effects on T cells. Fifteen SLE patients, fulfilling the ACR 1982 criteria, starting RTX and followed longitudinally up to two years, were analyzed for B- and T- lymphocyte subsets using multicolor flow cytometry. DN were defined as IgD-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 40 publications
0
9
0
Order By: Relevance
“…Meanwhile, IFN-a-induced Tph cells could induce B cell differentiation into plasmablasts (60). In contrast, one study found no significant alteration in Tph cells after treatment with rituximab, suggesting that Tph cells do not change in response to disease activity (61). SS is a systemic autoimmune disease which is characterized by lymphocytic infiltration of exocrine glands, mainly salivary and lacrimal glands (79).…”
Section: Aih (73) 2020mentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, IFN-a-induced Tph cells could induce B cell differentiation into plasmablasts (60). In contrast, one study found no significant alteration in Tph cells after treatment with rituximab, suggesting that Tph cells do not change in response to disease activity (61). SS is a systemic autoimmune disease which is characterized by lymphocytic infiltration of exocrine glands, mainly salivary and lacrimal glands (79).…”
Section: Aih (73) 2020mentioning
confidence: 99%
“…Mounting studies have been conducted to investigate the physiological role and mechanisms of Tph cells, predominantly focusing on autoimmune diseases (shown in Table 1 ), including RA ( 6 , 7 , 48 , 52 54 ), SLE ( 26 , 55 61 ), SS ( 62 66 ), IgG4-related disease (IgG4-RD) ( 64 , 67 ), type 1 diabetes (T1D) ( 68 , 69 ), primary biliary cirrhosis (PBC) ( 70 ), immunoglobulin A nephropathy (IgAN) ( 71 ), juvenile idiopathic arthritis (JIA) ( 72 ), autoimmune hepatitis (AIH) ( 73 ), dermatomyositis (DM) ( 74 ), celiac disease (CeD) ( 58 ), systemic sclerosis (SSc) ( 58 ), autoimmune bowel disease (IBD) ( 75 ), and psoriasis vulgaris (PV) ( 76 ). Notably, most studies elucidated altered frequencies of Tph cells and their correlation with disease activity, and they analyzed only cTph cells because of the relative difficulty in obtaining tissue samples.…”
Section: Tph Cells In Human Autoimmune Diseasesmentioning
confidence: 99%
See 1 more Smart Citation
“…found that belimumab, a monoclonal antibody targeting the B cell cytokine BAFF, can decrease the ABCs with early clinical improvements in SLE in a prospective cohort study ( 101 ). Consistent with these findings, another clinical study showed that SLE patients who received rituximab treatment had a reduction of ABCs frequency at early follow-up ( 54 ). Besides, it was found that ABCs were reduced following plasma exchange treatment with a reduction in all immunoglobulin subsets in the circulation in patients with MS ( 102 ).…”
Section: Abcs-a Potential Therapeutic Targetmentioning
confidence: 54%
“…CD19+ B cell depletion is a marker for rituximab’s biologic effect and, despite some authors ( 41 ) have found an association with disease remission and clinical response, this has not always been the case. The effect of rituximab on B cells is transient and some variability across patients in the response is expected, which can be partially explained by the reduction of the frequency of specific B cell subsets and phenotypes that can differ between patients ( 53 ). The study by Jónsdóttir et al showed that patients with low baseline levels of CD19-positive lymphocytes can also respond to depletion with rituximab, due to the lack of correlation between peripheral blood and the rest of the population of CD19-positive B cells in the lymphoid tissues ( 20 ).…”
Section: Discussionmentioning
confidence: 99%